2014
DOI: 10.36961/si15166
|View full text |Cite
|
Sign up to set email alerts
|

Umfrage Produktionstechnik – regionale Unterschiede in der Zuckerrübenproduktion

Abstract: Für den Zuckerrübenanbau in Deutschland werden seit 1994 durch die Expertenschätzung der Umfrage Produktionstechnik Daten auf Basis der Anbauregionen der Zuckerfabriken erhoben. Zwischen den einzelnen Regionen lassen sich für verschiedene Parameter deutliche Unterschiede aufzeigen. Die durchschnittliche Schlaggröße variiert zwischen den Regionen von 3 ha in der Region Süd bis über 25 ha in der Region Nord-Ost. Der Getreideanbau ist in allen Regionen die wichtigste Vorfrucht vor Zuckerrüben. Der Winterweizen n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, cropping intervals of less than 2 years are not recommended for sugar beet (Götze et al 2017). In most studies, different crops such as winter wheat, winter barley, maize, potato, dry bean, pea, oat and timothy has been grown before sugar beet as preceding crops (Märländer et al, 2003;Buhre et al, 2014;Larney et al, 2016;Götze et al, 2017;Koch et al, 2018). Koch et al (2018) found no dramatic yield loss in sugar beet as a consequence of shorter sugar beet cropping intervals and highlighted the influence of year and grower management on yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, cropping intervals of less than 2 years are not recommended for sugar beet (Götze et al 2017). In most studies, different crops such as winter wheat, winter barley, maize, potato, dry bean, pea, oat and timothy has been grown before sugar beet as preceding crops (Märländer et al, 2003;Buhre et al, 2014;Larney et al, 2016;Götze et al, 2017;Koch et al, 2018). Koch et al (2018) found no dramatic yield loss in sugar beet as a consequence of shorter sugar beet cropping intervals and highlighted the influence of year and grower management on yield.…”
Section: Introductionmentioning
confidence: 99%